2003
DOI: 10.1108/13683040310466690
|View full text |Cite
|
Sign up to set email alerts
|

Performance measurement tools: the Balanced Scorecard and the EFQM Excellence Model

Abstract: Performance improvement is high on the agenda of many companies around the world and with the growing number of improvement models now available care has to be taken to adopt an approach that will yield the most attractive return on investment. This paper compares and contrasts two widely known and wellpublicized improvement models: Kaplan and Norton's Balanced Scorecard and the EFQM Excellence Model. Each consists of a non-prescriptive template offering managers a relatively small number of categories of key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0
21

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(143 citation statements)
references
References 9 publications
2
120
0
21
Order By: Relevance
“…Price (2003) had suggested an integration of BSC and BEM into strategic management processes to enhance continuous improvement. Wongrassamee et al (2003) argue that both academic and industry practitioners agree that both BSC and BEM measurement tools are useful for enhancing business performance and continuous improvement, but are sceptical of how managers can identify the key performance indicators from their corporate strategy. Andersen et al (2000) reported that BEM can be used at two different levels: at the passive level to act as checklist for configuring the strategic vision, values and strategy of organisations; and at the active level BEM provides a health check of organisations performance and identifies areas for improvement.…”
Section: Developing a Performance Measurement System (Pms)mentioning
confidence: 99%
“…Price (2003) had suggested an integration of BSC and BEM into strategic management processes to enhance continuous improvement. Wongrassamee et al (2003) argue that both academic and industry practitioners agree that both BSC and BEM measurement tools are useful for enhancing business performance and continuous improvement, but are sceptical of how managers can identify the key performance indicators from their corporate strategy. Andersen et al (2000) reported that BEM can be used at two different levels: at the passive level to act as checklist for configuring the strategic vision, values and strategy of organisations; and at the active level BEM provides a health check of organisations performance and identifies areas for improvement.…”
Section: Developing a Performance Measurement System (Pms)mentioning
confidence: 99%
“…Park's managers, experts and elites determine these values in Semnan university science and Technology Par using a continuous improvement. In this article based on Fig 3 and using technique of group analytical hierarchy process (AHP), we determined importance and indices values (Wongrassamee et al, 2003).…”
Section: Establishment and Executingmentioning
confidence: 99%
“…Shahin et al (2012) tried to integrate those two business models while other authors tried to show the synergic effects of their parallel implementation (Lamotte & Carter, 2000;Dror, 2008, Yang, 2009Lua, Bettsa, & Croom, 2011). However, Wongrassamee et al (2003) adopted a critical attitude towards those models and suggested instead the adoption of strategic frameworks to specific types of organizations, since the BSC and EFQM model are considered as non-prescriptive models which they regarded as a weakness.…”
Section: Managing and Measuring Business Quality: The Framework Of Rementioning
confidence: 99%